The Representation of Obsession in Korean Drama (Study on the Movie “Door Lock”) - Kartina Yusva; Sapta Sari; Asnawati Asnawati (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2022)
This study aims to see the representation of obsession by showing repetitive thoughts and being obsessed with getting something desired. The methodology used in this study is descriptive qualitative with Roland Barthes' semiotic analysis method consisting of denotation, connotation and myth. Through the selection of scenes in which there were elements of obsessive violence, there is an obsession between mysterious men and women, indicated by various kinds of physical violence, such as murder, cutting off organs, hands and feet, and drugging women. A mysterious man is obsessed with a woman named Jo Kyung Min because he has a feeling of wanting to be near her. This violence also illustrates the distance from the norms of truth, ethics, and disrespect for others. Judging from the obsessive violence carried out by the man involving the closest person to Jo Kyung Min, his best friend at work and the person above his apartment being victims of physical violence, this mysterious man has psychopathic thoughts, and the desire of a man to add a woman against the opposite sex but unseen, so he does a strange thing which is to try to enter Jo Kyung Min's apartment and sleep next to her, because of an uncontrollable desire.